Determining the effect of pre-treatment in rice noodle quality subjected to dehydration through hierarchical scoring - Ismail, Muhammad Heikal; Hii, Ching Lik; Routray, Winny; Woo, Meng Wai (Multidisciplinary Digital Publishing Institute, 2021)
Fresh rice noodle was usually coated in a large amount of oil to avoid stickiness and extend the shelf life. Pre-treatment has been applied to reduce the quantity of oil in rice noodle. In this research, the pre-treatment and temperature effect on the rice noodle quality subjected to hot air drying, heat pump drying, and freeze drying was investigated. Texture, color, oil content, and starch gelatinization of the dried noodle was further evaluated. Results revealed that there were significant differences (p < 0.05%) in texture, color, oil content, and starch gelatinization in rice noodle subjected to pre-treatment. Furthermore, the texture, color, oil content, and starch gelatinization demonstrated a significant difference (p < 0.05%) in freeze drying rather than hot air drying and heat pump drying. The findings indicate that the qualitative features of the dehydrated noodle are synergistic to pretreatment and drying temperature. Despite superior quality shown by freeze drying, the hierarchical scoring has proven that rice noodle undergoing hot air drying at 30 °C to produce comparable quality attributes. The hierarchical scoring can be a useful tool in quality determination for the food industry.